The neuroregenerative influence to treadmil exercise in striata from mice intoxicated with methamphetamine - Freitas, Hugo José Fernandes de (2015)
Dissertação de mestrado em Patologia Experimental, apresentada á Faculdade de Medicina da Universidade de Coimbra